Recovery stress perception and salivary cortisol behaviour of swimmers in different training periods - Simola, R.; Prado, L. S.; Samulski, D. M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Many investigations have studied the psychological, physiological and biochemical responses of athletes to different load training periods with the aim to monitor more precisely the load training effects. However, those studies have been showing different results (Coutts et al. 2007). Therefore, we investigated the effects of different training loads on stress and recovery perception (SRP) and salivary cortisol (SC) in different training periods. Methods: Subjects were highly trained, male swimmers (17.7 + 1.3 y.o.). SRP and SC were evaluated after three distinct training phases (T1, T2 and T3). In T1, subjects swam approximately 50.000 meters in a week. After one month (T2), swimmers covered an average of 45.000 meters in a week with a higher intensity. In T3, after a month, swimmers covered an average of only 25.000 meters. SC were measured through enzymatic immunoassay. SRP was evaluated using the questionnaire RESTQ-Sport for the Portuguese language (Costa & Samulski, 2005). The Anova one-way with repeated measures and Pearson`s product moment correlation were used for statistical analysis. P<0.05. Results: From T1 to T3, it were observed a significant reduction in RESTQ-Sport scales, Fatigue (2,28 + 1,11; 1,12 + 0,71), Lack of Energy (2,33 + 0,93; 1,5 + 0,61), and an increase in SC (0,23 ìg/dL + 0,15; 0,47 ìg/dL + 0,19). Between T2 and T3, it were observed a reduction in Fatigue (2,29 + 1,08; 1,12 + 0,71), Lack of Energy (2,02 + 0,84; 1,5 + 0,61), Disturbed Breaks (2,0 + 0,7; 1,23 + 0,75), and an increase in SC (0,38 ìg/dL + 0,15; 0,47 ìg/dL + 0,19). From T1 to T2, there were significant augments in SC (0,23 ìg/dL + 0,15; 0,38 ìg/dL + 0,19). It were observed significant correlations between SC and SRP only in T1, in scales Social Recovery (p=0,002), General Well Being (p=0,031) and Disturbed Breaks (p=0,034). Conclusion: Different load training may cause changes on SRP and SC. However, psychological stress (SRP) may not necessarily be correlated with the physiological stress (SC). Moreover, the results highlight that it is necessary different variables to monitor the load training more precisely and that the SC can show the same behaviour direction when the load training is increased or decreased.